Implementasi MD5 dan Paillier Cryptosystem Untuk Membuat Tanda Tangan Digital - Benny Sinaga; Muhammad Abdul Rohim; Efori Bu'ulolo (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Of the several benefits of cryptographic techniques is data authentication. Before the digital era, signatures were used as a means to prove the authenticity of printed documents such as letters, certificates, certificates, books and so on. Documents that do not have a signature will be doubtful for their authenticity. One of the characteristics of these signatures is that all the signature patterns are the same, so this situation can easily be manipulated with signature forgery, if the related parties use a different signature on each document that is signed it will also have an impact on changing doubts on the parties who are signed. reserves the right to verify. To overcome the need, documents should be given a digital signature. The intended digital signature is not a manual signature that is scanned and then embedded in a digital document. Digital signatures will be built from cryptographic techniques. In this study, the signature that will be used is a signature with a combination of a hash function algorithm and a web-based public-key cryptography. The methods used are the MD5 algorithm and Paillier Cryptosystem. Paillier cryposystem is a public-key cryptographic algorithm which is believed to be difficult to attack because it uses n-residue class calculations so that it will be very difficult to find the key pair used, this is known as the Composite Residuosity (CR) assumption.